Dry-season retreat and dietary shift of the dart-poison frog Dendrobates tinctorius (Anura: Dendrobatidae) - Marga Born; Frans Bongers; Erik H. Poelman; Frank J. Sterck (Phyllomedusa: Journal of Herpetology, 2010)
Seasonal rainfall affects tropical forest dynamics and behaviorof species that are part of these ecosystems. The positive correlation between amphibian activity patterns and rainfall has been demonstrated repeatedly. Members of Dendrobatidae, a clade of Neotropical dart-poison frogs, are well known for their habitat use and behavior during the rainy season, but their behavior during the dry season has received little attention. We studied habitat use and diet of the dendrobatid frog Dendrobates tinctorius in French Guiana during the rainy and dry seasons. Unlike many other dendrobatid frogs, D. tinctorius does not maintain territories for the entire rainy season. Both sexes colonize recently formed canopy-gaps and stay in these forest patches for only a few weeks. The frogs inthese patches consume a great diversity of prey, consisting of ants, beetles, wasps, insect larvae, and mites. During the dry season, frogs move to retreat sites in mature forest, such as palm bracts and tree holes. The frogs are less active and consume fewer prey items in the dry season, and they consume fewer wasps and insect larvae, but more termites. Ants are the most common prey items during both the wet and dry seasons. We discuss the effects of shifts in seasonal habitat use on the territorial behavior of dendrobatid frogs.